Youth at stake : how gambling puts the young at risk of losing more than they bargain for - Chen, Meiyue (2009)
Youth at stake explores the local youth gambling scene as young gamblers share their stories. It covers how they start, what problems can arise, and how some struggle to quit. This issue is especially relevant now with the imminent opening of Singapore’s first legalised casinos. Recent research also continues to show that young gamblers are more likely to get into trouble for their gambling behaviour. Experts also give their take on local gambling trends.